ANALYSING THE INCIDENCE, ETIOLOGY, AND PATTERNS OF MANDIBULAR FRACTURES IN INDIAN SUB-POPULATION: A CROSS-SECTIONAL STUDY - Dr. Tirumalrao; Dr. Jyothi L.; Dr. Bapugouda Mulimani; Dr. Amarvarma; Abhishekha Patil; Shweta Danaraddi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND: Mandibular fractures are common facial injuries with varying patterns influenced by demographic factors. Understanding these patterns can inform better prevention and treatment strategies. This study aimed to analyze the incidence, etiology, and patterns of mandibular fractures in patients treated at the Raichur Institute of Medical Sciences (RIMS). METHOD: This retrospective study was conducted at the RIMS, a public health hospital in the Raichur region of Karnataka State, over a two-year period, from April 2022 to April 2024. Data were collected from medical records and radiographs of patients diagnosed with mandibular fractures. The study analysed demographic data, etiological factors, anatomical distribution, and treatment outcomes. Statistical analysis was performed using SPSS version 26.0, with chi-square tests for categorical variables (p < 0.05 considered significant). RESULT: The study included 742 patients. The majority (64.2%) were in the 20-40 age group, with males representing 77.8% of cases. MVAs were the leading cause of fractures (47.0%), followed by falls (25.3%) and assaults (17.5%). Alcohol involvement was noted in 64.4% of cases. The symphysis region was most commonly fractured (59.4%), with angle para-symphysis opposite fractures being the most common pattern (40.6%). Most patients (72.9%) underwent ORIF as the treatment modality. Significant associations were found between demographic factors (age, gender, marital status, alcohol involvement) and fracture patterns and mechanisms of injury (p < 0.05). CONCLUSION: This study provides a comprehensive understanding of the demographic factors, mechanisms, and patterns of mandibular fractures. The majority of cases occurred in the 20 to 40 age group, predominantly affecting males, with MVAs as the leading cause. Alcohol involvement was a significant factor. These findings underscore the need for tailored prevention and treatment strategies, particularly focusing on high-risk groups and alcohol-related incidents.